Advances in antigens associated with Idiopathic Membranous Nephropathy - Shan-Shan Li; Dong-E Tang; Yong Dai (Journal of the Formosan Medical Association, 2021)
Membranous nephropathy (MN) is a common cause of nephrotic syndrome in adults. Idiopathic MN (IMN), one of the forms of MN, usually has an unknown etiology. IMN is described as an autoimmune disease, and its pathogenesis is quite complex. The discovery of the M-type phospholipase A2 receptor (PLA2R) plays an important role in promoting our understanding of IMN, although the exact mechanisms of its occurrence and development are still not completely clear. Other target antigens have been discovered one after another, as considerable progress has been made in the molecular pathomechanisms of IMN. Here, we review the findings about the target antigens associated with IMN in recent years. It is hoped that this article can provide researchers with some scientific issues or innovative ideas for future studies of IMN, which will provide clinicians with more knowledge about further improving their abilities to provide better medical care for IMN patients.